2018
DOI: 10.1515/jls-2018-2001
|View full text |Cite
|
Sign up to set email alerts
|

The metaphorical conceptualization of sadness in the Anglo-Saxon elegies

Abstract: The aim of this paper is to explore the predominant metaphorical conceptualization of sadness in three Old English elegiac monologues whose main themes are the pain and solitude of exile and separation. Taking as a starting point the Cognitive Theory of Metaphor and briefly reviewing the experimental evidence that supports the experiential grounding of our conceptualization of sadness, as well as our own previous research on the Old English expressions for emotional distress, we analyze the use of sadness meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
1
0
1
Order By: Relevance
“…Conceptualizations of human emotions have been a research topic of great interest in linguistics, for there have been many studies on various emotion concepts, such as ANGER (Glynn, 2014;Kahumburu, 2016;Yu, 1995), FEAR (Caballero & Díaz-Vera, 2021;Oster, 2010Oster, , 2012, HAPPINESS (Nguyen, 2016;Rajeg, 2019;Stefanowitsch, 2004), JEALOUSY (Díaz-Vera & Caballero, 2013;Ogarkova, 2007), LOVE (Gawda, 2019;Glynn, 2002), PRIDE (Soares da Silva, 2020), SADNESS (Verdaguer & Castaño, 2018), and SHAME (Krawczak, 2014a(Krawczak, , 2014b(Krawczak, , 2018. These studies have revealed that, in contemporary language use, human emotions are often understood or conceptualized in metaphorical terms (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Conceptualizations of human emotions have been a research topic of great interest in linguistics, for there have been many studies on various emotion concepts, such as ANGER (Glynn, 2014;Kahumburu, 2016;Yu, 1995), FEAR (Caballero & Díaz-Vera, 2021;Oster, 2010Oster, , 2012, HAPPINESS (Nguyen, 2016;Rajeg, 2019;Stefanowitsch, 2004), JEALOUSY (Díaz-Vera & Caballero, 2013;Ogarkova, 2007), LOVE (Gawda, 2019;Glynn, 2002), PRIDE (Soares da Silva, 2020), SADNESS (Verdaguer & Castaño, 2018), and SHAME (Krawczak, 2014a(Krawczak, , 2014b(Krawczak, , 2018. These studies have revealed that, in contemporary language use, human emotions are often understood or conceptualized in metaphorical terms (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…9 Además, insiste en que su compañero es el dolor (v. 30 -sorg to geferan) y que posee profundas heridas del corazón (v. 49 heortan benne). Observamos en algunas de estas expresiones la correlación entre el dolor del alma y el clima invernal que detallaremos más adelante (Verdaguer -Castaño 2018).…”
unclassified